MATERIAL NARRATIVES IN THE CREATION OF WORKS OF ART: ANALYSIS OF THE ROLE OF MATERIALS IN THE FORMATION OF VISUAL AND CONCEPTUAL MEANING - Yanuar Ikhsan Pamuji; Bagja, Bachrul Restu; Wahyudi, Luqman (Acintya, 2024)
The creation of works of art by artists always involves forming a narrative that they want to convey to the audience. The narrative depends on the artist's interest in the chosen theme and how the theme is articulated through visual elements. Usually, narratives in works of art are realized through metaphorical forms that describe the idea or message to be conveyed. On the other hand, materials in the creation of works of art are often considered as supporting elements that complete the metaphor. This research aims to explore how materials in works of art can form their own narrative, not just as complementary objects. Materials are also entities that contribute to the overall meaning of the work. By analyzing the relationship between material and narrative, this research provides insight into how material can be interpreted as a visual language. Materials have narrative potential, revealing more than their function in the formal structure of the work of art.